Peningkatan Ketrampilan Kader Aisyiyah dalam Perawatan Pasien Stroke di Rumah - Ekan Faozi; Rizki Anjarsari; Sherly Nur Janah (PPNI UNIMMAN, 2023)
Stroke is one of several priority health problems that is often reported by the Gemolong Community, Sragen. Strokes do not only attack the elderly, but people of productive age can experience strokes. Stroke events can be prevented by reducing risk factors for stroke, and proper management of stroke attacks can prevent morbidity and mortality. This community service activity aims to increase the knowledge and skills of Aisyiyah administrators in promoting stroke prevention and handling stroke attacks appropriately. The methods used in service activities are training and simulation which includes program outreach, providing education about stroke prevention and treatment. The output of the service, namely the participants' knowledge and skills regarding stroke prevention and treatment, increases. This can be seen from the increasing pre-test and post-test results. Likewise, regarding the cadre's skills in how to treat stroke sequelae with bed transfer and ROM, the cadre is able to demonstrate bed transfer and ROM correctly according to what has been taught.